COMBINATION OF FRENOTOMY AND GINGIVECTOMY TREATMENT WITH LASER DIODES AS AESTHETIC CORRECTIONS: A CASE REPORT - Onge Victoria Hendro; Vincent Laksono; Chiquita Prahasanti (Dentino : Jurnal Kedokteran Gigi, 2020)
ABSTRACTBackground: High tension on the frenum in some cases may generate chronic inflammation. Chronic inflammation can trigger gingival enlargement, thereby resulting in unfavorable aesthetic appearance. Frenotomy and gingivectomy are surgical procedures that are often performed in periodontics field to overcome such condition. The use of lasers in frenectomy/frenotomy and gingivectomy methods is still uncommon but more convenient than using a scalpel. Diode lasers exhibit several advantages over conventional methods because it can control the bleeding and is also painless that may reduce the need of anesthesia. Objectives: To report the likelihood of diode lasers instead of conventional methods using scalpels in frenotomy and gingivectomy for aesthetic corrections. Case: A 20-years-old female patient arrived at Periodontics Department of Airlangga University to repair gums in upper and lower jaw region. Patient felt less confident with the state of her gum which discerned to cover the portion of her teeth and wished to receive surgical treatment for aesthetics improvement. No involvement of systemic disease and drug consumption was noted in this case. Case Management: The management of such aberrant frenum was accomplished by performing labial frenotomy and removing enlarged tissues which is a common surgical procedure in the field of periodontics. Dental lasers are currently being employed in manyfields of periodontics, providing alternatives to traditional scalpel techniques. Conclusion: Surgical treatment in cases of aberrant frenum and gingival enlargement using diode lasers (Epic X, Biolase) for aesthetic correction provides satisfactory results with minimum pain and rapid healing. Keywords: Aberrant frenum, Diode laser ,Frenotomy, Gingivectomy